1999
DOI: 10.1038/sj.ejcn.1600770
|View full text |Cite
|
Sign up to set email alerts
|

Energy density of the diet, food volume and energy intake by age and sex in a healthy population

Abstract: Objective: To assess the changes in energy intake (EI), food intake volume (FV) and energy density (ED) related to age and gender in a population in the Mediterranean area of Spain, and to determine the different role of FV and ED on the consecution of the adequate EI throughout lifespan. Subjects: One thousand and eighty-eight individuals (1 ± 65 y) randomly selected from the population census. Design: Cross-sectional study in which food intake was quanti®ed by 24 h dietary recall, three non-consecutive days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 21 publications
6
32
0
1
Order By: Relevance
“…The highest energy intakes were now associated with the lowest consumption of key nutrients. Higher energy intakes have also been associated with higher energy density of the diet in both epidemiological and clinical research (Poppitt and Prentice, 1996;Marti-Henneberg et al, 1999). In this study, the lower-cost diets were the most energy dense and contained the least key nutrients.…”
Section: Discussionmentioning
confidence: 63%
“…The highest energy intakes were now associated with the lowest consumption of key nutrients. Higher energy intakes have also been associated with higher energy density of the diet in both epidemiological and clinical research (Poppitt and Prentice, 1996;Marti-Henneberg et al, 1999). In this study, the lower-cost diets were the most energy dense and contained the least key nutrients.…”
Section: Discussionmentioning
confidence: 63%
“…Some of them found a positive relationship between ED and weight (10,14,15,19) , whereas some others found no significant association (13,20) or only in men (16) . Among the few longitudinal analysis available in free-living subjects, two were performed in women only (21,22) and one in both sexes (23) .…”
Section: Body Fat Distribution: Cohort Studies: Diet Quality: Energy mentioning
confidence: 96%
“…Some studies have reported positive associations between ED and EI (4,10,11) . In addition, there is a strong correlation between the ED of foods and their fat content (4,12) , which may also encourage weight gain.However, the results from cross-sectional epidemiological studies that have examined the relationships between dietary ED and body-weight status are not consistent (10,13 -20) .Some of them found a positive relationship between ED and weight (10,14,15,19) , whereas some others found no significant association (13,20) or only in men (16) . Among the few longitudinal analysis available in free-living subjects, two were performed in women only (21,22) and one in both sexes (23) .…”
mentioning
confidence: 99%
“…However, the study of dietary energy density in free-living persons is a new effort, and data on this issue are scarce. Observational studies generally found a direct association between energy intake and energy density (Marti-Henneberg et al, 1999;Cox and Mela, 2000;Stubbs et al, 2000;Stookey, 2001;Darmon et al, 2004). All these studies mainly focused on the association between energy density with energy and macronutrient intake and in some cases, additionally, with body mass index (BMI) (Marti-Henneberg et al, 1999;Cox and Mela, 2000;Stubbs et al, 2000;Cuco et al, 2001;Stookey, 2001;Darmon et al, 2004;Ledikwe et al, 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies generally found a direct association between energy intake and energy density (Marti-Henneberg et al, 1999;Cox and Mela, 2000;Stubbs et al, 2000;Stookey, 2001;Darmon et al, 2004). All these studies mainly focused on the association between energy density with energy and macronutrient intake and in some cases, additionally, with body mass index (BMI) (Marti-Henneberg et al, 1999;Cox and Mela, 2000;Stubbs et al, 2000;Cuco et al, 2001;Stookey, 2001;Darmon et al, 2004;Ledikwe et al, 2006b). Recently published data from two large-scale epidemiological studies indicate that high-energy density diets were a risk factor for higher BMI (Kant and Graubard, 2005;Howarth et al, 2006;Ledikwe et al, 2006a;Mendoza et al, 2007).…”
Section: Introductionmentioning
confidence: 99%